Ethics in undergraduate nursing degrees: An international comparative education study - Papastavrou, Evridiki; Chiappinotto, Stefania; Gastmans, Chris; Igoumenidis, Michael; McCabe, Catherine; Suhonen, Riitta; Palese, Alvisa (My University, 2024)
Ensuring morally competent nurses depends on many factors, such as environmental, social, political, and cultural. However, several inadequacies in nursing education have been documented, and no common framework has been established for how nursing ethics should be taught in undergraduate education.
Keywords: Curriculum; Ethical courses; Ethics; Nursing; Undergraduate education